1987
DOI: 10.1093/carcin/8.11.1691
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivation of N-nitrosopiperidine to mutagens: role of hepatic cytochrome P-450 proteins and contribution of cytosolic fraction

Abstract: In the present study the role of two families of cytochrome P-450 proteins and the contribution of the cytosolic fraction in the activation of N-nitrosopiperidine to mutagens in the Ames test were investigated. The bioactivation of this nitrosamine was preferentially catalysed by the phenobarbitone-induced cytochromes P-450, in contrast to the 3-methylcholanthrene-induced cytochromes P-448. The mutagenicity of nitrosopiperidine catalysed by microsomes, in the absence of cytosol, was lower when compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…An interesting and unexpected observation was that the microsomal activation of 2-aminofluorene could be supported by NADH. Similar observations have been reported for other carcinogens such as nitrosopiperidine [8], dimethylnitrosamine [24] and the S9-mediated activation of 2-acetylaminofluorene [25]. It may be con-cIuded that an NADH-dependent microsomal enzyme can catalyse the Noxygenation of 2-aminofluorene or, alternatively, certain cytochrome P-450 families may utilise NADH as the only electron donor.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…An interesting and unexpected observation was that the microsomal activation of 2-aminofluorene could be supported by NADH. Similar observations have been reported for other carcinogens such as nitrosopiperidine [8], dimethylnitrosamine [24] and the S9-mediated activation of 2-acetylaminofluorene [25]. It may be con-cIuded that an NADH-dependent microsomal enzyme can catalyse the Noxygenation of 2-aminofluorene or, alternatively, certain cytochrome P-450 families may utilise NADH as the only electron donor.…”
Section: Discussionsupporting
confidence: 80%
“…The cytosol is believed to be devoid of any role in the initial oxidation of chemical carcinogens and to be involved exclusively in the furt her metabolism of the oxidation products produced by microsomes. Incorporation of the cytosolic fraction into the microsomal activation system in the Ames test can markedly enhance the mutagenic effect of chemicals such as benzo[a]pyrene, aflatoxin B, [3], 2-aminofluorene [4], 2-acetylaminofluorene [5], 2-amino-3-methylimidazo-(4,5-:f)quinoline [6], benzidine [7] and N-nitrosopiperidine [8].…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have indicated that NADH can also accelerate the oxidative metabolism of p-nitrophenetole 9) and p-nitroanisole, 10,11) and the bioactivation of 2-acetylaminofluorene 12) and nitrosoamines. 13,14) During our studies on the microsomal oxidative metabolism of D…”
mentioning
confidence: 99%
“…Both Aroclor 1254 and isoniazid caused the induction of CYP1 and CYPB2E, respectively. The CYP1 catalyses the bioactivation of PAHs and HAs, and CYP2B catalyses the bioactivation of nitrosoamines, such as nitrosopyrrolidine and NP (Ayrton et al, 1987).…”
Section: Discussionmentioning
confidence: 99%